Inclusion of the fractured level into the construct of short segment fixation in patients with thoracolumbar fractures: clinical and radiological outcome - Ali R. Hamdan (SpringerOpen, 2021)
Abstract Background Thoracolumbar fractures represent a widespread injuries that can cause significant disability and strain the healthcare system. Different surgical approaches are described in the literature. This study was conducted to evaluate the fractured level inclusion in short-segment fixation of thoracolumbar junction spine fractures. Results Preoperative neurological deficit was reported in seven patients ranging from ASIA grade C to D. All of these patients improved to grade E by the end of the follow-up period, except for one patient who improved from grade C to D. The mean Oswestry Disability Index was 19.87%. The mean postoperative Cobb angle was 11.77° which significantly improved compared to a preoperative value of 19.37°. There was a significant improvement in the postoperative anterior and posterior vertebral body height compared to the preoperative values. The vertebral body compression ratio significantly improved during the postoperative period to a mean of 84% compared to 76% preoperative. Conclusions There was significant improvement of the postoperative values of the mean Cobb angle, the anterior and the posterior vertebral body height as well as the vertebral body compression ratio compared to the preoperative values.